2018
DOI: 10.1158/0008-5472.can-18-0855
|View full text |Cite
|
Sign up to set email alerts
|

PTTG and PBF Functionally Interact with p53 and Predict Overall Survival in Head and Neck Cancer

Abstract: Head and neck squamous cell carcinoma (HNSCC) is the 6th most common cancer worldwide and poses a significant health burden due to its rising incidence. Although the proto-oncogene pituitary tumor-transforming gene 1 (PTTG) predicts poor patient outcome, its mechanisms of action are incompletely understood. We show here that the protein PBF modulates PTTG function, is overexpressed in HNSCC tumors, and correlates with significantly reduced survival. Lentiviral shRNA attenuation of PTTG or PBF expression in HNS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 47 publications
3
13
0
Order By: Relevance
“…These findings indicate that higher expression of PTTG3P, PTTG1 and PTTG2 is connected with activation of prosurvival and protumorigenic downstream genes by mutant p53 protein. Indeed, our observations are supported by the results obtained by Read et al; however, their analysis focused solely on PTTG1 [ 34 ]. In our work, we separately examined the roles of PTTG3P , PTTG1 and PTTG2.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…These findings indicate that higher expression of PTTG3P, PTTG1 and PTTG2 is connected with activation of prosurvival and protumorigenic downstream genes by mutant p53 protein. Indeed, our observations are supported by the results obtained by Read et al; however, their analysis focused solely on PTTG1 [ 34 ]. In our work, we separately examined the roles of PTTG3P , PTTG1 and PTTG2.…”
Section: Discussionsupporting
confidence: 90%
“…TCGA data analysis of breast cancer patients performed by Lou et al showed a positive correlation between the PTTG3P pseudogene and TP53 signaling pathways [ 33 ]. Moreover, Read et al reported that PTTG1 and PBF ( PTTG1IP , PTTG1 interacting protein) together modulate the interaction with TP53, reduce p53 protein stability and affect its downstream targets which lead to worse outcomes in HNSCC patients [ 34 ]. Our results indicated that expression levels of PTTG3P , PTTG1 and PTTG2 depend on TP53 mutation type.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Squamous cell carcinoma of the head and neck (SCCHN) is the sixth most common tumor worldwide, with approximately 650,000 cases being reported annually over the past few decades [1,2]. Despite advances in therapeutic strategies, the 5-year survival rate for SCCHN has not significantly improved, and this lack of improvement is due to late diagnosis, frequent loco-regional recurrences at the primary site, and cervical lymph node metastasis [3,4].…”
Section: Introductionmentioning
confidence: 99%